Dielectric and ferroelectric characteristics of 0.7PZT-0.3PZN ceramics substituted with Sr - Vittayakorn N. (2014)
Lead zirconate titanate-lead zinc niobate (PZT-PZN) ceramics with compositions close to the morphotropic phase boundary were investigated as a function of Sr doping. The powders were prepared using the columbite- (wolframite) precursor method. Dielectric and ferroelectric properties of the as-sintered and annealed samples were measured. The results showed that with increasing Sr concentration dielectric constant versus temperature curves become gradually broader. Sr doping has been shown to produce a linear reduction in the transition temperature (Tm) (294.1-12.7x °C) with concentration (x). The maximum value of the dielectric constant decreased and the degree of diffuse phase transition was enhanced with Sr doping. However, the results indicated that the degree of disorder in Sr-modified PZT-PZN was further improved by thermal annealing. After thermal annealing at 900°C for 48 h a strong enhancement of dielectric constant (εr) and remanent polarization (Pr) was observed. © 2005 IOP Publishing Ltd.